The Effect of Self-Esteem and Gender on the Work Performance of FM Radio Announcers in Tegal - Imam Riyadi; Sigit Pamungkas (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The pursuit of popularity is a common goal for individuals working in the entertainment industry, including male and female radio announcers at private stations. Despite the common assumption that female announcers should achieve higher success due to their professional skills, data suggests that male announcers outperform their female counterparts. This discrepancy can be attributed to cultural influences on Self-Esteem based on gender. This study aimed to investigate the relationship between Self-Esteem, Gender, and Job Performance among FM radio announcers in Tegal, with a focus on the simultaneous and partial effects of these factors. Self-Esteem is conceptualized as an individual's self-assessment of personal worth, while Gender refers to the experiences perceived as masculine or feminine. Job performance encompasses various aspects, including quantity, quality, ability, attitude, dedication, and cooperation. To gather data, a questionnaire was distributed among FM radio announcers in Tegal using a saturated sampling technique. The results revealed that both Self-Esteem and Gender collectively explained 56.2% of the variance in Job Performance among the announcers. The t-values for Self-Esteem and Gender were found to be 4.82 and 5.33, respectively, both of which were greater than the t-table value of 1.68, indicating statistical significance. These findings suggest that Self-Esteem and Gender have a notable impact on the job performance of FM radio announcers in Tegal. The study highlights the importance of understanding how cultural and psychological factors influence professional achievement in the entertainment industry, and calls for further research to explore how gender-based cultural influences shape career success in different sectors of the media industry.